Physicochemical surface properties of nonencapsulated and encapsulated coagulase-negative staphylococci. - van der Mei, H C (1989)
Cell surfaces of three nonencapsulated and three encapsulated coagulase-negative staphylococci were characterized by their surface free energies, zeta potentials, and elemental and molecular compositions. Surface free energies were calculated from contact angle measurements with various liquids. All six strains showed a high surface free energy (103 to 126 mJ.m-2), estimated from the concept of polar and dispersion components. However, the hydrogen-donating surface free energy parameter was zero for all nonencapsulated strains. The zeta potential profile measured as a function of pH in phosphate-buffered saline for the nonencapsulated strains was completely different from that of the encapsulated strains. X-ray photoelectron spectroscopy was used to determine the elements (O, C, N, P, and K) in the outer 2 to 5 nm of the freeze-dried cell surface and showed that the hydrophilic character of the staphylococci was related to oxygen (O/C ratio, approximately 0.52)- and phosphorus (P/C ratio, approximately 0.03)-containing groups. Both the elemental and molecular characterizations (done by infrared spectroscopy) pointed to the presence of polysaccharides and polypeptides on the cell surface of the nonencapsulated and encapsulated strains.